The influence of structural changes to the tourist industry in Montenegro - Adžić Slavica; Đurašević Silvana (Turističko Poslovanje, 2017)
The influence of transition on the society has reflected on the entire social-economic circumstances in Montenegro. This complex and long process has changed the stability of economic growth and the development of the national economy and has effectuated the structural changes in the economy of Montenegro. Beside transition, the war in the surroundings, international isolation and numerous other problems, which have changed flows of the social and economic development, have affected the condition of the economy system. On the example of other surrounding countries, Montenegro has persevered to provide, through the process of structural reforms, more rational and efficient company market business dealings. This paper investigates to which extent and in which manner the structural changes have reflected onto the tourist industry and which results have been achieved on the basis of reforms which should provide for the joining with the flows of European and World development. By changing the company's state-legal status, the state has strived to provide a greater level of economical activity, productivity growth, degree of participation in the social product, national revenue and employment. According to national economy aggregate indicators, the structural changes have not yet provided the balance of the entire economy to a sufficient extent. Social, economic and political stability are the assumptions for tourism development which is very sensitive to numerous changes in economy and in the society.